Kalimat Larangan dalam Al-Qur’an (Analisis Terhadap Larangan Durhaka Kepada Kedua Orang Tua dalam Qs. Al-Isra Ayat 23) - Said, Ibnu Furkan; Abubakar, Achmad; Irham, Muhammad (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
This research aims to analyze the definition of prohibited sentences in the Koran. A prohibition is a demand to abandon an action from a higher party. This article explains the various structures of prohibitive sentences in the Al-Qur'an, which give rise to various variations in meaning depending on the perspective from which a commentator analyzes them. Apart from that, this article also explores the prohibition on disobedience to parents in Qs. al-Isra/17:23 based on the interpretation of the ulama. This research provides results with the first main interpretation, the prohibition sentence is a demand to abandon an action from a higher party, namely a demand to abandon something ordered by Allah SWT. Second, the prohibition sentence has several forms including; Prohibited sentences are in the form of sharih (clear), non-sharih, rhetorical form of kalam khabar (statement), and rhetorical form of kalam istifham (question). Third, in Qs. al-Isra/17:23, there are also obligations of a child to his parents, namely not to speak harshly or not to shout at them for bad actions, to speak good words to them, to humble themselves before their parents, and to ask for love from Allah for them. both, namely praying for both of them to be given grace.